The otherness of animal intelligence - Sarosiek, Anna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Book review: Recenzja książki: Frans de Waal, Are We Smart Enough to Know How Smart Animals Are?, W. W. Norton & Company, Inc., New York, 2016, ss. 473